(3TQM MeGSI CHj JeGes - (3CHi GdMLGL jhSa Hf SdjeGf Hf YjSis; (3CHh JeGe GdWGFj , CHh JeGe MHjH Hf ChS Hf GdMGQK GdWGFj,J (B231 (3g` s ((3TGWHI(B-(3GdCfOdS s)
(3ChdgG (B:s
(3Ke HYO GdMeO ddg hGdKfGA hGdCYJQGa HSGHY GdfYeGA hddeYJVO HGddg GdefUhQ ef GdCHGOi GdLejdg h GdVGFY GdSfI hGdeff GdeJhGdjg GdYXjeI s
(3BNQgG (B:s
(3acdeG gHJ LGO hcQe CVMi bQi ddefGjG Ci WYeg dgG MjK eGJ cGf jWYegG ef GdCbQGf ai GdLRH ced GdSaQ GdChd s
(3HChdgG hbajI Ydi LGeY GdRjJhfg HJhfS HJGQjN (B1256(3g`s
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs